Culturally safe and ethical biomarker and genomic research with Indigenous peoples-a scoping review - Rebecca Dal Pra; Penny O'Brien; Huong X. T. Nguyen; Joanne Luke; Robyn A. Smith; Adrienne Withall; Kylie Radford; Louise M. Lavrencic; Rosie Watson; Leon Flicker; Dina Logiudice (BMC, 2024)
Abstract Background Indigenous peoples globally continue to be underrepresented in biomarker, genomic, and biobanking research. The aim of this study was to identify core components of culturally safe and ethical biomarker and genomic research with Indigenous peoples in Australia, Aotearoa/New Zealand, Canada and the USA. Methods A scoping review with a systematic search strategy was conducted utilising electronic databases MEDLINE, EMBASE, PsychINFO, CINAHL and Global Health. Key search terms included 'biomarkers' and 'genomics' research involving Indigenous peoples in relation to ethical and legal principles of respect, sovereignty, governance and existing policies. Original research studies published from the year 2000 to the 1st of August 2023 were reviewed in a systematic manner. Components of culturally safe and ethical research processes were identified and synthesised descriptively. The quality of included studies was assessed using an Aboriginal and Torres Strait Islander Quality Appraisal Tool through an Indigenous lens. Results Seven interrelated research components were identified from seventeen studies as core processes to enhance the cultural safety of biomarker and genomic research. These included building relationships and community engagement, learning, research coordination, logistics, consent, samples and biospecimens, biobank structures and protections and policy. The importance of ensuring self-determination, ownership and decision-making power is emphasised in processes to establish and conduct biomarker and genomic research with Indigenous peoples. Conclusions Components that contribute to the cultural safety of biomarker and genomic research processes identified in this scoping review were assembled into a theoretical framework to guide research practice. Further evaluation is required by Indigenous peoples and communities to appropriate and adapt this framework for local use to promote the cultural safety of research processes and minimise barriers to Indigenous peoples' participation in biomarker and genomic research.